The main causes of death contributing to absolute and relative socio-economic inequality in Italy. (November 2018) - Alicandro, G.; Sebastiani, G.; Bertuccio, P.; Zengarini, N.; Costa, G.; La Vecchia, C.; Frova, L.
Abstract: Objectives: Monitoring socio-economic inequality has become a priority for many governments, especially after the socio-economic changes that followed the 2008 financial crisis. This study aimed at detecting the causes of death with the largest socio-economic inequality in relative and absolute terms in Italy. Study design: This is a historical cohort study. Methods: We used two regression-based measures of socio-economic inequality, the relative index of inequality (RII) and the slope index of inequality (SII), to rank the causes of death with the highest relative and absolute socio-economic inequality. We obtained these measures on a large census-based cohort study with more than 35 million individuals and 452, 273 deaths registered in the period 2012–2014. Results: The causes with the highest relative socio-economic inequality were the following: laryngeal cancer (RII: 6.1, 95% confidence interval [CI]: 4.8–7.78), AIDS/HIV (RII: 4.8, 95% CI: 3.1–7.4), chronic liver disease (RII: 4.8, 95% CI: 3.2–7.3), and chronic lower respiratory diseases (RII: 4.8, 95% CI: 3.5–6.5) in men, and diabetes (RII: 6.2, 95% CI: 4.8–7.9), AIDS/HIV (RII: 4.5, 95% CI: 2.7–7.7), genitourinary system (RII: 3.8, 95% CI: 2.6–5.4) and chronic liver diseases (RII: 3.6, 95% CI: 2.9–4.5) in women. In absolute terms, lung cancer and ischemic heart diseases contributed more to the overall socio-economic inequality in men, whereas diabetes and ischemic heart diseases accounted for most of the socio-economic inequality in women. Conclusions: Our findings call for effective policies to reduce the disparities in mortality from ischemic heart diseases, lung cancer, and diabetes taking into account the sex-specific pattern of inequality. Highlights: Inequality measured in relative and absolute terms have different public health implications. High relative inequality for AIDS, diabetes, and chronic liver diseases in both sexes. High relative inequality for cancers of upper aerodigestive tract in men. Lung cancer made the highest contribution to overall absolute inequality in men. Diabetes and circulatory diseases contributed the most in women.